Manajemen Mutu di Organisasi Sekolah - Ramlan, Ramlan; Muhamad Rahmatuloh, Muhamad Rahmatuloh; Adi Ismawadi, Adi Ismawadi; Naufal Syahrul Anwari, Naufal Syahrul Anwari; Endang Supiani, Endang Supian; Hanafiah, Hanafiah; Muchtarom, Muchtarom (PT. Solusi Komunikasi Terapan, 2024)
This research examines Organizational Quality Management in Schools. Education is a process to prepare humans to live better and more prosperously in facing the future. The quality of education is a key factor in increasing the capacity and ability of an educational institution, which aims to meet the demands of students and society so that they are able to adapt in the future. The decline in the quality of education in Indonesia in general can be seen from the low quality of graduates, the poor national education system and the low level of human resources. The quality of education needs to be managed in an orderly and sustainable manner to bring satisfactory results. So quality management is needed in school organizations. This research method is literature study research, by collecting data from several articles. The research results show that education quality management is moving educational institutions to continually and continuously increase the capacity and ability of their institutions to meet the demands of students and society so that they are able to adapt amidst the progress of globalization.